Quick Response and Retailer Effort - Krishnan, Harish; Kapuscinski, Roman; Butz, David A. (Management Science, 2010)
The benefits of supply chain innovations such as quick response (QR) have been extensively investigated. This paper highlights a potentially damaging impact of QR on retailer effort. By lowering downstream inventories, QR may compromise retailer incentives to exert sales effort on a manufacturer's product and may lead instead to greater sales effort on a competing product. Manufacturer-initiated quick response can therefore backfire, leading to lower sales of the manufacturer's product and, in some cases, to higher sales of a competing product. Evidence from case studies and interviews shows that some manufacturers view high retailer inventory as a means of increasing retailer commitment (“a loaded customer is a loyal customer”). By implication, manufacturers should recognize the effect we highlight in this paper: the potential of QR to lessen retailer sales effort. We show that relatively simple distribution contracts such as minimum-take contracts, advance-purchase discounts, and exclusive dealing, when adopted in conjunction with QR, can remedy the distortionary impact of QR on retailers' incentives. In two recent antitrust cases we find evidence that, consistent with our theory, manufacturers adopted exclusive dealing at almost the same time that they were making QR-type supply chain improvements.